Reflections on the development of psychology in Hongkong society students, teachers, and academic institutions.[article]. - Ho, David Y. F.
This papers reviews the development of psychology in Hongkong society, focusing especially on the academic sphere. Encouraging achievements are noted, although serious problems arising from the transplantation of Western psychology into foreign soil may be discerned. Remarks by psychology teachers, made in private, reflect their concern that there is a basic incompatibility between the conceptual approach and the values of Western psychology, as they are taught to the student, and the readiness with which then students are willing or able to integrate them into their lives. The remarks also point to a remarkable encapsulation and retreat from self-knowledge among students. it is argued that a radical change in the approach of psychology in Hongkong is needed: to help students to relate psychology to life, and more generally, to work toward a creative synthesis of Eastern and Western ideas- to create a new psychology, one which has indigenous roots and which will not leave the individual with a sense of alienation from his culture.